Corruption, institutions and regulation - Michael Breen; Robert Gillanders (University College Dublin, UCD School of Economics, 2011)
We analyze the effects of corruption and institutional quality on the quality of business regulation. Our key findings indicate that corruption negatively affects the quality of regulation and that general institutional quality is insignificant once corruption is controlled for. These findings hold over a number of specifications which include additional exogenous historical and geographic controls. The findings imply that policy-makers should focus on curbing corruption to improve regulation, over wider institutional reform.
Keywords: 330; Business Regulation; Economic Policy; Institutional Quality; Corruption